THE IMPORTANCE OF GENERAL AND SPECIAL EXERCISES IN DEVELOPING THE PHYSICAL FITNESS OF FOOTBALL PLAYERS - Irmatov Dilyorbek Yunusbekovich (Bright Mind Publishing, 2026)
This article examines the importance of general and special exercises in the development of football players’ physical fitness from both scientific-theoretical and practical perspectives. In the course of the study, the effectiveness of special exercises in developing key physical qualities of football players—such as speed, strength, agility, and endurance—was analyzed using experimental and control groups. The obtained results demonstrated that training sessions organized on the basis of special exercises contribute to the stable and purposeful development of football players’ physical qualities. The findings substantiate the necessity of scientifically integrating general and special exercises in the process of football training.
Keywords: Physical fitness of football players, general physical exercises, special physical exercises, sports training, physical qualities, experimental group, control group, sports pedagogy, training effectiveness.